CORROSION RATE OF COPPER AND IRON IN SEAWATER BASED ON RESISTANCE MEASUREMENT - W.H. Rahmanto; , Gunawan; Rahmad Nuryanto (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Copper and iron metal wire corrosion in artificial sea water have been investigated in three corrosion systems, in the (i) closed bath, (ii) opened or air exposed bath, and (iii) aerated bath. The aim of our investigation is to determine the effect of oxygen contained in the air to the metals’ corrosivity. Artificial sea water was prepared by dissolving 173.59 g sodium chloride and 4.91 g potassium chloride in 7.00 kg of water at 230C.The corrosion experiment was carried out under the constant temperature of 32 0C. Decrease of metal masses during corrosion was monitored by measuring the metal resistance change. Our experiment provided the corrosion rate in g.cm-2.s-1 as 4.01 x 10-7 (in closed bath), 4.01 x 10-6 (in opened bath) and 9.43 x 10-6 (in aerated bath) of copper metal, and 2.12 x 10-6 (in closed bath), 5.99 x 10-6 (in opened bath), and 1.07 x 10-5 (in aerated bath) of iron metal. Experimental results show that air oxygen give strong effect on the corrosion of copper and iron metal